GENDER AND LANGUAGE USE IN ACADEMIC DISCOURSE: EMPOWERING WOMEN'S VOICES - Sylvia, Sylvia; Syarifudin, Albitar Septian (Transpublika Publisher, 2023)
This research paper explores the complex relationship between gender and language use within the context of academic discourse. By examining the ways in which language both reflects and shapes gender dynamics, this study highlights the potential of language as a tool for cultural change, particularly in empowering women's voices in academic settings. In particular, it investigates the role of feminist language reform in challenging traditional patriarchal narratives that often marginalize female perspectives and contributions in scholarly environments. This paper aims to demonstrate how adopting gender-sensitive language practices can facilitate a more inclusive academic discourse, thereby dismantling stereotypes around femininity and establishing a more equitable platform for women's voices in the academic realm. The findings of this study indicate that the implementation of gender-sensitive language guidelines has led to a significant increase in women's participation and visibility within academic publications and conferences.